P66 Patient-reported outcomes in patients with cystic fibrosis with homozygous for the Phe508del CFTR mutation on lumacaftor-ivacaftor treatment: results from an observational study. (11th November 2022) - Arooj, P; Morrissy, D; Ronan, N; McCarthy, Y; Fleming, C; Eustace, JA; Murphy, DM; Plant, BJ
Abstract : Background: Previous studies showed that lumacaftor-ivacaftor (LUMA-IVA) provides meaningful clinical benefits in patients with cystic fibrosis who are homozygous for the Phe508del CFTR mutation. However, little is known about the patient perspectives and overall health related quality of life (HRQoL) following lumacaftor-ivacaftor initiation. Methods: Forty -four adult CF patients with homozygous for the Phe508del CFTR mutation were evaluated at baseline and prospectively three monthly for one-year post commencement of lumacaftor-ivacaftor using validated questionnaires assessing fatigue level (Functional Assessment of Chronic Illness Therapy -Fatigue (FACIT-fatigue) scale, sleep quality (Pittsburgh Sleep Quality Index (PSQI) score), sinonasal symptoms (Modified version of Sino-Nasal Outcome Test (SNOT-22), mental health (Patient Health Questionnaire -9 (PHQ-9) and General Anxiety Disorder-7 (GAD-7)) and CF-related quality of life (Cystic Fibrosis Questionnaire Revised (CFQ-R). Results: We observed mean +6.8± 13.0 (p=0.001) improvement in respiratory, mean+4.7±15.7 (p=0.04) improvement in body image and mean +16.1±36.0 (p=0.003) improvement in weight domains of CFQ-R. Mean -0.61 ± 1.9 (p=0.043) reduction in global PSQI score and sustained mean -3.0± 4.3 reduction (p=0.000) in modified SNOT-22 score one year after LUMA-IVA treatment were noted. No change or worsening in anxiety and depression scores (GADS-7 and PHQ-9) were reported. Conclusion: Lumacaftor-ivacaftor combination resulted in significant benefits in rhinologic QoL, sleep quality and respiratory, body image and weight domains of a disease -based tool cystic fibrosis questionnaire -revised (CFQ-R). Patient report outcome from CF patients suggest that LUMA-IVA treatment is associated with improved overall quality of life in PWCF. Multicentre, larger studies are required to further quantify the impact of LUMA-IVA on patient reported health and well being outcomes.